Assessing the impact of Span 60 and cholesterol on mupirocin niosomes developed for topical delivery - Fareed, Noor Yousif; Naji, Ghada Hamid; Al-Zheery, Worood Hameed (Pharmakeftiki, 2025)
Mupirocin (MUP), a broad-spectrum antibacterial agent, is commonly used in order to treat superficial skin infections. However, its therapeutic efficacy is limited by poor skin permeability and the impracticality of prolonged topical administration. This study reports the development of a niosomal delivery system engineered so as to enhance topical MUP delivery by optimizing vesicle size and drug entrapment efficiency. Niosomes were prepared using the thin-film hydration method, and a 22 full factorial design was employed in order to optimize formulations based on Span 60 and cholesterol concentrations. Vesicle size and entrapment efficiency served as dependent variables. Both models were significant, thereby indicating that formulation variables and their interactions substantially influenced vesicle characteristics. The findings demonstrate that a full factorial design is an effective approach to elucidate and optimize the impact of formulation variables on MUP-loaded niosomes.